Enzymatic Conversion of RNA from Yeast Extract to Guanosine monophosphate (a flavoring agent) - Makendran, Raja (My University, 2012)
Ribonucleotides such as 5’-guanosine monophosphate (5’-GMP) and 5’-inosine monophosphate (5’-IMP) are important flavor enhancers. They improve the taste of food and have a synergistic effect with monosodium glutamate (MSG). 5’-GMP was synthesized enzymatically by hydrolysis of RNA to a mixture of Ribonucleotides by 5’-phosphodiesterase enzyme (5’-PDE). Yeast extract, which is produced from the extraction of yeast cells, consists primarily of amino acids, peptides, nucleotides and other soluble components of yeast cells. RNA content in yeast is typically in the order of 7-12% (w/w). Yeast cell of Saccharomyces cerevisiae as a by-product from bioethanol industry was used as a convenient starting material for production of yeast extract. This microorganism has a status as generally recognized as safe (GRAS), and are considered safe as food ingredient. Yeast extract was obtained from a simple method of autolysis process. 5’-phosphodiesterase enzyme (5’-PDE) were extracted and partially purified from germinated mung bean seeds. This partially purified enzyme was used for hydrolysis of RNA in the yeast extract to produce 5’-GMP-rich yeast extracts. The effect of autolysis time, enzyme concentration and hydrolysis (incubation) time on 5’-GMP content in the yeast extract was examined.
Keywords: Biokemi och molekylärbiologi; Livsvetenskaper; Biochemistry and Molecular Biology; Life Science